Development and Evaluation of the Transdermal Drug-delivery System of Isradipine using Various Natural Polymers - Kola, Venu (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Transdermal applications, relative to other routes, are non-invasive, requiring the simple adhesion of a “patch” resulting in better patient compliance, improved bioavailability of a drug, and easy treatment termination. Hence, this investigation was aimed at delivering isradipine across intact skin as a membrane-moderated transdermal therapeutic system of Eudragit RL100, Eudragit RS100, and Eudragit E100. Materials and Methods: An UV spectrophotometric analytical method was developed for isradipine using a double UV spectrophotometer. The method was validated for linearity, accuracy, and precision. Isradipine was determined in triplicate by standard techniques. In vitro release studies in triplicate was conducted in Keshary-Chien diffusion cells across depilated rat’s abdominal skin. Hypersensitivity reaction testing on depilated rabbit’s skin was conducted. Stability of the drugs was studied under accelerated conditions recommended by ICH (40°C/75% R.H) for 90 days. Drug content was obtained periodically and compared. Log Kp of isradipine was found to be –5.337. Flux obtained from basic in vitro release (1 mg/ml) studies of isradipine was found to be 0.081 mg/cm2/h (r = 0.985). Results: The flux from isradipine from reservoir gels IX and IA was found to be 0.034 mg/cm2/h (r = 0.985) and 0.033 mg/cm2/h (r = 0.987), respectively. The flux of membrane-moderated systems of isradipine IXRL, IARL, IXRS, IARS, IXE, and IAE was found to be 0.022 mg/cm2/h (r = 0.977), 0.021 mg/cm2/h (r = 0.979), 0.020 mg/cm2/h (r = 0.977), 0.020 mg/cm2/h (r = 0.978), 0.019 mg/cm2/h (r = 0.975), and 0.016 mg/cm2/h (r = 0.970), respectively. Isradipine permeates greater from xanthan gum (IX) gel compared to almond gum gel and lowest flux of the series was found to be from almond gum. Kp also tends to decrease. It was understood from the investigation that IX and almond gum can be used as drug reservoirs and Eudragit RL100, Eudragit RS100, and Eudragit E100 can be exploited as rate controlling polymeric membrane. Conclusion: The formulations released the drug in adequate amount and it is also contemplated in this study that even when used on human skin therapeutic concentration could be achieved in the treatment of hypertension.